Nanostructured Multilayer Composite Films of Manganese Dioxide/Nickel/Copper Sulfide (MnO2/Ni/CuS) Deposited on Polyethylene Terephthalate (PET) Supporting Substrate. - Awangku Nabil Syafiq, Awangku Metosen; Suh, Cem Pang; Suk, Fun Chin (Hindawi Publishing Corporation, 2015)
Nanostructured multilayer manganese dioxide/nickel/copper sulfide (MnO2/Ni/CuS) composite films were successfully deposited onto supporting polyethylene terephthalate (PET) substrate through the sequential deposition of CuS, Ni and MnO2 thin films by chemical bath deposition, electrodeposition, and horizontal submersion deposition techniques, respectively. Deposition of each thin-film layer was optimized by varying deposition parameters and conditions associated with specific deposition technique. Both CuS and Ni thin films were optimized for their electrical conductivity whereas MnO2 thin film was optimized for its microstructure and charge capacity. The electrochemical properties of nanostructured multilayer MnO2/Ni/CuS composite films were evaluated by cyclic voltammetry as electrode materials of an electrochemical capacitor prototype in a dual planar device configuration. Cyclic voltammogram in mild Na2SO4 aqueous electrolyte exhibited a featureless and almost rectangular shape which was indicative of the ideal capacitive behavior and high cycling reversibility of the electrochemical capacitor prototype. Nanostructured multilayer MnO2/Ni/CuS composite films on supporting polyethylene terephthalate (PET) substrate could potentially be utilized as electrode materials for the fabrication of high performance electrochemical capacitors.